2021
DOI: 10.4236/ojneph.2021.112020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Severe Anemia (Hb ≤ 5 g/dl) in Non-Dialyzed Chronic Renal Failure Patients in the Nephrology and Hemodialysis Department of Point G University Hospital

Abstract: Introduction: Chronic renal failure (CRF) is defined as glomerular filtration rate (GFR) less than 60 ml/min/1.73m 2 for at least three (3) months. Anemia is one of its most common complications. Anemia increases the risk factor for cardiovascular mortality by 18% per gram of hemoglobin loss. Objectives: To determine the prevalence and characteristics of this severe anemia, to determine the indications for transfusion, the complications related to this anemia, the evolution and the prognosis of these patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…We found that impairment of general condition was the main reason for hospitalization with a proportion of 30.2%. This result was different from that of Open Journal of Blood Diseases Seydou et al who noted renal failure in 85.2% of cases [10]. Pallor and asthenia were the most common clinical signs with prevalences of 88.3% and 86% respectively.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…We found that impairment of general condition was the main reason for hospitalization with a proportion of 30.2%. This result was different from that of Open Journal of Blood Diseases Seydou et al who noted renal failure in 85.2% of cases [10]. Pallor and asthenia were the most common clinical signs with prevalences of 88.3% and 86% respectively.…”
Section: Discussioncontrasting
confidence: 78%
“…Haemolytic anaemia is a relatively rare condition as epidemiological studies have found an incidence of approximately 3 cases/100,000 population per year in the Western world [5]. This figure does not reflect reality, as it does not take into account the forms associated with other pathologies that are sometimes in the forefront [10]. In 2021, Garrigue et al found a prevalence of 65.7% in France [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, long-term chronic anemia can be used to explain other complications, especially the cardiovascular system. Seydou Sy et al pointed out in the latest study in 2021 that anemia was closely related to myocardial hypertrophy [ 37 ]. As CKD patients are often complicated with sodium and water retention in the body, chronic anemia and hypoxia, the heart has a long-term compensatory function to ensure sufficient oxygen supply to the peripheral circulation.…”
Section: Discussionmentioning
confidence: 99%